Laser-evoked potentials in painful radiculopathy. Issue 11 (November 2017) - Hüllemann, P.; von der Brelie, C.; Manthey, G.; Düsterhöft, J.; Helmers, A.K.; Synowitz, M.; Gierthmühlen, J.; Baron, R.
Highlights: Laser-evoked potential (LEP)-latency shifts indicate pronounced nerve root damage, worsening of function, severity, and pain. Only full or nearly full abolishment of the N2/P2 amplitude indicates clinical relevance. LEPs help to differentiate between moderate and severe nerve root compression. Abstract: Objective: The aims of this exploratory study were (1) to develop a standardized objective electrophysiological technique with laser-evoked potentials to assess dorsal root damage quantitatively and (2) to correlate these LEP measures with clinical parameters and sensory abnormalities (QST) in the affected dermatome. Methods: Thirty-eight patients with painful radiculopathy and 20 healthy subjects were investigated with LEP recorded from the affected dermatome and control areas as well as with quantitative sensory testing. Questionnaires evaluating severity and functionality were applied. Results: On average, LEP amplitudes and latencies from the affected dermatomes did not differ from the contralateral control side. In patients with left L5 radiculopathy (more severely affected) the N2 latency was longer and the amplitudes reduced. Conclusions: The N2P2 amplitude correlated with pinprick evoked sensations in QST. The N2 latency from the affected dermatome correlates with pain intensity, chronicity, clinical severity and with a decrease of physical function. Significance: An increase in N2-latency indicates a more pronounced nerve root damage, which is associated with a decrease of function and an increase of severity and pain. LEP amplitudes are associated with the functional status of the nociceptive system and may distinguish between degeneration of neuronal systems and central sensitization processes.